2011
DOI: 10.1002/bjs.7479
|View full text |Cite
|
Sign up to set email alerts
|

Oesophagogastrectomy and pancreatoduodenectomy for caustic injury

Abstract: PD can save the lives of patients with caustic injuries extending beyond the pylorus, but has poor functional outcome. Immediate pancreatic duct reconstruction should be preferred to duct occlusion to decrease the rate of pancreatic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…We also recorded a significantly higher incidence of pathologically proven full-thickness duodenal wall necrosis after acid ingestion. This finding is in accordance with the high proportion of acid ingestion reported by our group after pancreatoduodenectomy for caustic injuries [16]. Of note, the incidence of early oropharyngeal burns and of pharyngeal strictures was similar after ingestion of acids and alkalis; occurrence of pharyngeal injuries is most likely to be conditioned by the pattern of ingestion (hesitation before swallowing, provoked vomiting) rather than the nature of the ingested agent [15].…”
Section: Discussionsupporting
confidence: 89%
“…We also recorded a significantly higher incidence of pathologically proven full-thickness duodenal wall necrosis after acid ingestion. This finding is in accordance with the high proportion of acid ingestion reported by our group after pancreatoduodenectomy for caustic injuries [16]. Of note, the incidence of early oropharyngeal burns and of pharyngeal strictures was similar after ingestion of acids and alkalis; occurrence of pharyngeal injuries is most likely to be conditioned by the pattern of ingestion (hesitation before swallowing, provoked vomiting) rather than the nature of the ingested agent [15].…”
Section: Discussionsupporting
confidence: 89%
“…These publications have shown that salvage resections are associated with increased morbidity and mortality compared to elective procedures. In contrast, very few data are available on primary emergency pancreas resections as these procedures are rarely performed [10][11][12][13][14]. In the present study, we could show that emergency pancreas operations account to a frequency below 1 % in a tertiary referral center with a high overall number of pancreatic operations and full 24/7 emergency service.…”
Section: Discussioncontrasting
confidence: 73%
“…Most publications on primary emergency pancreatic operations are dealing with the management of pancreatic injuries following blunt or penetrating abdominal trauma [6][7][8][9]. Beyond these publications on trauma patients, the available literature mainly includes case reports or small patient series [10][11][12][13][14] and show that there is heterogeneity in the indications leading to emergency pancreas operations as well as in the performed surgical procedures [10,11]. However, considerable morbidity and mortality rates have been reported.…”
Section: Abstract Pancreatic Surgery Emergency Morbiditymentioning
confidence: 99%
“…Moreover, a large series of 18 patients affected by caustic injuries in which an EPD was associated with oesophagogastrectomy has been reported by Lefrancois, with a mortality rate of 39% (N ¼ 7/18) [49].…”
Section: Discussionmentioning
confidence: 95%